The Relationship between Discipline and Learning Achievement of Class XI Students at SMA PGRI 4 Padang - Wahydi, Adek (Holistic Science, 2022)
The background of this research is that there are students who are late doing the assignments given by the teacher, there are students who do not do the assignments when the assignments are done at home, there are students who often copy friends' assignments. This study aims to determine: 1) Discipline of students in Class XI SMA PGRI 4 Padang. 2) Learning achievement of students in Class XI SMA PGRI 4 Padang. 3) The relationship between discipline and student achievement in Class XI SMA PGRI 4 Padang.  This type of research is descriptive quantitative. The population of this study were students of class XI, totaling 50 students. The sampling technique was carried out using a total sampling technique, namely as many as 53 students who became the research sample. The analysis used in this research is percentage and correlation.  The results of this study indicate: 1) The discipline of students in Class XI SMA PGRI 4 Padang is in the high category. 2) The learning achievement of students in Class XI SMA PGRI 4 Padang is in a fairly good category. 3) There is a relationship between discipline and student achievement in Class XI SMA PGRI 4 Padang with quite strong cohesiveness. This research is recommended to students so that they can further improve discipline in the family, school and social environment by knowing and complying with applicable rules and norms.